1997
DOI: 10.1007/bf02439968
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the clinical management of patients with tinnitus

Abstract: The current management in tinnitus of sensorineural origin is reviewed. Epidemiological data demonstrates that 90% of patients with hearing loss experience some tinnitus. Approximately 1% of the population suffer from a chronic tinnitus that causes severe distress and requires some type of management intervention. Present non-surgical therapies include masking techniques, psychological counseling, and biofeedback. There are also a number of drugs that have been applied, the most common being antidepressants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Jastreboff [36] reported that tinnitus occurred in 85% of patients with ear problems, and 90% of patients with hearing loss were recorded in Parnes' study [24] , but still, some patients complain of tinnitus without obvious hearing loss [37] . However, hearing loss has been consistently associated with tinnitus, and it is generally accepted that 70-80% of deaf people have tinnitus, and only 20-30% do not [5,38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jastreboff [36] reported that tinnitus occurred in 85% of patients with ear problems, and 90% of patients with hearing loss were recorded in Parnes' study [24] , but still, some patients complain of tinnitus without obvious hearing loss [37] . However, hearing loss has been consistently associated with tinnitus, and it is generally accepted that 70-80% of deaf people have tinnitus, and only 20-30% do not [5,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Jastreboff and Jastreboff [23] reported that tinnitus affected approximately 17% of the general population and creates a significant problem in approximately 4-5% of them. Parnes [24] reported that as many as 35-45% of the adult population experience tinnitus at some time, but that only 1% of the population suffers from symptoms that are clinically and emotionally distressing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatments are largely ineffective, with great variability in patient response and risk for significant adverse effects [41,42]. While the pathophysiology is still unclear, it is generally accepted that maladaptive plasticity within auditory circuitry of the CNS is at least, in part, responsible for chronic tinnitus [43].…”
Section: Preclinical and Clinical Studies For Tinnitusmentioning
confidence: 99%
“…Either on its own or in combination with other auditory or vestibular symptoms (e.g., as in Meniere's disease), tinnitus is a debilitating condition which affects all aspects of life and sometimes even leads to suicide. Parnes (1997) estimated that approximately 1% of the population suffers from chronic tinnitus which causes distress and that 90% of patients with hearing loss experience some tinnitus.…”
Section: Introductionmentioning
confidence: 99%